UNIVERSITY STUDENTS’ CRITICAL THINKING IN WRITING ARGUMENTATIVE ESSAYS (RETAIN, 2015)
Abstract The ability to think critically is very important for students to acquire since it could assist them in solving problems. Critical thinking requires looking at an issue from several standpoints before reaching a final decision. One of the ways to teach critical thinking is through writing especially argumentative writing. All processes in constructing an argumentative essay require the writers to think critically. Regarding to the importance of critical thinking in writing argumentative essays, university students are the most appropriate subject of this study. Therefore, the subject of this research is the students in English Department of Unesa in 2013 academic year, particularly in Expository and Argumentative Writing B class. The objectives of this study are to identify how the students use critical thinking to construct argumentative essays and to describe how critical thinking is reflected in the students’ argumentative essays. This research is descriptive qualitative research. There are two points that can be seen in the result of this research. First, the students had reflected their critical thinking by involving the characteristics of critical thinking as proposed by Cottrell’s theory in their argumentative essays very well. While the second point, the students used their critical thinking to construct argumentative essay very well especially in choosing the topic, organizing the arguments, and resolving problems that they experienced in constructing the essay. In conclusion, the students’ critical thinking was well applied in the writing of argumentative essay. Keywords: Critical thinking, argumentative essays, university students. Abstrak Kemampuan berpikir kritis sangat penting bagi siswa untuk memperoleh karena bisa membantu mereka dalam memecahkan masalah. Berpikir kritis memerlukan melihat masalah dari beberapa sudut pandang sebelum mencapai keputusan akhir. Salah satu cara untuk mengajarkan berpikir kritis adalah melalui menulis terutama menulis argumentatif. Semua proses dalam menulis sebuah esai argumentatif mengharuskan penulis untuk berpikir kritis. Mengenai pentingnya berpikir kritis dalam menulis esai argumentatif, mahasiswa adalah subyek yang paling tepat dalam studi ini. Oleh karena itu, subjek penelitian ini adalah mahasiswa Jurusan Bahasa Inggris Unesa pada tahun akademik 2013, khususnya di kelas Menulis Ekspositori dan Argumentatif B. Tujuan penelitian ini adalah untuk mengidentifikasi bagaimana siswa menggunakan pemikiran kritis untuk membuat esai argumentatif dan untuk mendeskripsikan bagaimana berpikir kritis direfleksikan dalam esai argumentatif siswa. Penelitian ini merupakan penelitian deskriptif kualitatif. Ada dua hal yang dapat dilihat dalam hasil penelitian ini. Pertama, siswa telah merefleksikan kemampuan berpikir kritis mereka dengan melibatkan karakteristik berpikir kritis seperti yang dikemukakan oleh teori Cottrell dalam esai argumentatif mereka dengan sangat baik. Sedangkan poin kedua, siswa menggunakan pemikiran kritis mereka untuk membuat esai argumentatif dengan sangat baik terutama dalam memilih topik, mengatur argumen, dan menyelesaikan masalah yang mereka alami dalam menulis esai. Kesimpulannya, kemampuan berpikir kritis siswa telah diterapkan dengan baik dalam penulisan esai argumentatif. Kata Kunci: Berpikir kritis, esai argumentatif, mahasiswa.